NHS Health Check programme: a protocol for a realist review - Duddy, C; Wong, GR; Gadsby, EW; Krska, J; Hibberd, V (BMJ Publishing Group, 2021)
Introduction The NHS Health Check aims to identify individuals at increased risk of cardiovascular diseases (CVDs) among the adult population in England. The Health Check includes calculation of CVD risk and discussion of pharmacological and lifestyle approaches to manage risk, including referral to lifestyle support services. The programme is commissioned by Local Authorities (LAs) and is delivered by a range of different providers in different settings. There is significant variation in activity, with uptake ranging from 25% to 85% in different areas, and clear evidence of variation in implementation and delivery practice. Methods and analysis We aim to understand how the NHS Health Check programme works in different settings, for different groups, so that we can recommend improvements to maximise intended outcomes. To do so, we will undertake a realist review and a survey of LA public health teams. Our review will follow Pawson’s five iterative stages: (1) locate existing theories, (2) search for evidence, (3) article selection, (4) extract and organise data and (5) synthesise evidence and draw conclusions. Our review will include documents describing local implementation alongside published research studies. We will recruit a stakeholder group (including Public Health England, commissioners and providers of Health Checks, plus members of the public and patients) to advise us throughout. Our survey will be sent to all 152 LAs in England to gather detailed information on programme delivery (including COVID-19-related changes) and available referral services. This will enable us to map delivery across England and relate these data to programme outcomes. Ethics and dissemination Ethical approval is not required for this review. For the survey, we have received approval from the University of Kent Research Ethics Committee. Our findings will be used to develop recommendations on tailoring, implementation and design strategies to improve delivery of the NHS Health Check in different settings, for different groups. PROSPERO registration number CRD42020163822.